Ethnicity and international security in the Far East from the perspective of national security. Issue 1 (2nd January 2016) - Zolotukhin, Ivan
Abstract : Ethnicity in the modern world impacts national domestic politics besides forming puzzles for the international environment. Simplifying ethnicity may result in obvious blunders, particularly regarding political issues. For instance, examining the ethno-political factor leads to the assumption that rioting ethnicity threatens both domestic and international securities, with ethnic conflicts having a powerful destructive potential. Amidst the global trends, ethnic processes are converting into a trigger of the contemporary international relations. This article aims to study the role of ethnicity as significant non-governmental actors from the perspective of national security in the Far East. The objectives of the study include researching contemporary security issues in Northeast Asia as well as novel possibilities for Russia in the process of the formation of the structures of security in Northeast Asia. The main aspect of the paper is to describe the ethnosystems of the Far East (the cases of Koreans, Tungus and Nanai) as independent coherent phenomena. It is important to show that international security is the major psychomental complex of the national system and via what mechanism this drive for international security may force adaptation by the ethnosystem. It is important to provide a concrete example of an ethnic process adapting to international security as an external pressure imposed externally. Methodology: This paper is based on the results of previous researches and findings, including the data containing information about the ethnopolitical situation in Northeast Asia as well as the interrelations among the neighbouring states and referred to the system analysis and the interdisciplinary approach.